Програмна система для управління діяльністю мережі медичних лабораторій - Мічурін, І. Є. (ХНУРЕ, 2023)
The article discusses the creation of a software system for managing the activities of a network of medical laboratories. The system is designed to automate typical processes in medical institutions and store all necessary information about patients. It consists of a server part, web and mobile client parts, and an IoT smart device. An interesting feature of the system is its ability to automatically collect data on air quality at the collection point and send it to the server. The article describes the project's business requirements, concept, scope, and limitations. The system's specification, design, and implementation are also discussed. Overall, the article presents a comprehensive overview of the development of a software system for managing the activities of medical laboratories